GENDER-NEUTRAL ASSESSMENT OF SPORTS ANXIETY: A COMPARATIVE STUDY ON BADMINTON AND TENNIS ATHLETES (International Journal of Food and Nutritional Sciences, 2023)
The objective of this research was to evaluate sports-related anxiety among athletes, with a focus on gender disparities and the specific sports discipline practiced. A sample of 100 participants, chosen based on their representation at the national level in tennis and badminton, was utilized. Anxiety levels were measured using the Sports Competition Anxiety Test (SCAT) questionnaire. Independent t-tests were employed to compare anxiety levels between male and female athletes in their respective sports, with a significance level set at 0.05. The analysis revealed that females exhibited higher anxiety levels compared to males, confirming their greater susceptibility to anxiety. The study identified that the utilization of thought control strategies and metacognitive beliefs among female athletes contributes to their vulnerability to emotional and neurotic challenges. Consequently, it is imperative for female athletes to adopt alternative coping strategies for managing difficult situations. The research proposes that female athletes could benefit from learning techniques to address metacognitive worries. Furthermore, modifying negative and positive metacognitive beliefs related to worry holds potential for enhancing mental well-being. In summary, this study provides empirical evidence of heightened anxiety levels among female athletes compared to their male counterparts. It underscores the importance of addressing mental health issues among female athletes and stresses the necessity of imparting effective anxiety management strategies. By fostering the development of adaptive metacognitive skills and adjusting their beliefs regarding worry, female athletes can bolster their psychological resilience and overall mental health.